Broiler Blood Profile Feeding Contained Fish Meal with Different Levels - Ismi Wardani; Takdir Saili; Muhammad Amrullah Pagala (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
The aim of the study was to analyze the blood profile of broilers fed with different levels of fish meal. The research design used a completely randomized design (CRD) with 4 treatments and 4 replications, so there were 32 experimental units. Each experiment consisted of 2 chickens and the chickens used were 100 broilers, with treatment P0 = Control (BP11 commercial feed), P1 = 43% Yellow Corn + 21% Bran + 27% CAB + 9% Fish Meal, P2 = 43% yellow corn + 23% bran + 22% CAB + 12% fish meal, P3 = 43% yellow corn + 25% bran + 17% CAB + 15% fish meal and the parameters observed were differential leukocytes. The results of the study with feeding containing fish meal with different levels had a significant effect (P<0.05) on the value of eosinophils, but had no significant effect (P>0.05) on the value of hematocrit, lymphocytes, heterophils, monocytes, basophils and H/L values. The conclusion of the study is that the provision of feed containing fish meal. The best treatment is in P3 by giving as much as 15% fish meal in the chicken ration.